Field performance of concrete pavement incorporating recycled concrete aggregate. (15th November 2016) - Sadati, Seyedhamed; Khayat, Kamal H.
Highlights: Fine and coarse RCA were used to produce concrete in laboratory. Coarse RCA was incorporated for casting pavement sections in field. Control specimens and core samples were used to monitor concrete properties. Instrumentation was employed for monitoring the in-situ deformations. Abstract: This paper reports test results of a field-oriented study carried out to demonstrate the performance of recycled concrete aggregate (RCA) for use in the construction of rigid pavement. Properties of eight concrete mixtures containing RCA were first compared to those of a reference mixture. Two mixtures proportioned with 30% and 40% of coarse RCA along with the reference concrete were then used for field implementation, which involved casting a 300-m long pavement section in St. Louis, Missouri. Samples were taken during slip-form pavement construction. Core samples were extracted at 120 days to determine in-situ properties. Instrumentation was incorporated to monitor the long-term deformation of different pavement sections. Incorporation of 30% and 40% RCA reduced the 91-day compressive strength by 7% and 12%, and the 56-day modulus of elasticity by 22% and 14%, respectively. The 56-day splitting tensile strength and flexural strength values of the two RCA mixtures were similar to those of the reference concrete. Mixtures exhibited similar performance in terms of durability against abrasion, freeze and thaw cycles, and rapid chloride ion permeability. An increase of 100 με in shrinkage was observed for the 40% RCA compared to the reference concrete. However, all field investigated mixtures exhibited similar long-term deformation patterns and magnitudes. In-situ deformation of all pavement sections was limited to 150 με at sensor locations.